Hábitos básicos de salud y creencias sobre salud y enfermedad en adolescentes de España, Colombia y México (2004)
The present study analyzes health habits in food, exercise and health beliefs in a sample of nine hundred and fifty fear adolescents, boys and girls (mean 12,36±2,06 years old) of different countries: Spain (321), Colombia (401) and México (232). All participants responded tea questionnaire with items related te health habits as well as health and illness beliefs. Results indicated that 58% of subjects show a risky food style, and 62,9% of subject show a risky physical activity, Comparisions among subjects of the three countries indicated that the Colombian sample had the worst food style while the spanish sample had the worst physical activity. Results also confirm that adolescence is a relevant moment in the formation of health beliefs with 61% and 54% of subjects showing respectively, an undefined pattern of beliefs or illness. Results show significant differences among the three countries.